Choice of location for Foreign Direct Investment by multinational corporations: Do tax burden matter? - Bassey, Evelyn; Amobi, Blessing Ndidiamaka; Okorie, Anthony Nwabuisi (Goodwood Publishing, 2022)
Purpose: This paper investigated the effect of the tax burden on the inflow of FDI into the continent. The study employed a panel data set of 48 SSA countries covering a period of 2009 to 2018. Research methodology: In other to account for the endogeneity problems associated with most financial data, we employed a dynamic panel two-step-system-GMM. Results: The result indicates that tax burden is a negative determinant of the inflow of FDI. In other words, multinational corporations attach a significant premium to countries with low tax burdens than those with a high tax burden. Similarly, an increase in the mobility of labour is a negative determinant of the inflow of FDI into the continent. All the economic and financial freedom indices included in the model have a positive and significant influence on the inflow of FDI into the continent. A sustainable tax policy that will lessen the tax burden on foreign investors should be formulated to enhance the inflow of FDI into the continent. Limitations: This study employed Dynamic System GMM which can produce variant results depending on the choice of instrument. Contribution: This study provides insight on the role of fiscal policy particularly taxation in explaining the inflow of FDI. Policymakers, multinational corporations, and other players in the global FDI market will appreciate the influence that tax exerts on FDI inflow.